Technology & education : issues, empirical research and applications - Wong, Su Luan; Md Khambari, Mas Nida; Silong, Abu Daud; Talib, Othman (Universiti Putra Malaysia Press, 2011)
This book is intended to be accessible to individuals with a special interest in the field of technology in education. It is addressed mainly for academicians, students, learners, policy makers and researchers. It comprises 15 chapters written by authors from Universiti Putra Malaysia (UPM), Universiti Sains Malaysia (USM), Universiti Teknologi Malaysia (UTM), Universiti Kebangsaan Malaysia (UKM), Universiti Pendidikan Sultan Idris (UPSI), Universiti Kuala Lumpur (UniKL), Taylor’s University, Southern College and Multimedia University (MMU). This publication is timely in promoting the development of technology integration in education, particularly in Malaysia.